2018
DOI: 10.1177/0300060518775835
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tip–apex distance and femoral head lag screw position on treatment outcomes of unstable intertrochanteric fractures using cephalomedullary nails

Abstract: BackgroundCephalomedullary nails are frequently used in unstable intertrochanteric fractures. The implant position is an important factor for surgical success. Thus, in the present study, finite element analysis methods were used to investigate the biomechanical behavior of five different cephalomedullary nail positions in unstable intertrochanteric fractures.MethodsFive different cephalomedullary nail implant positions were investigated. The observed indicators were the maximum displacement of the lag screw, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…The boundary condition was set as a fixation at the distal end of the femur, and the displacement along the x -, y - and z -axes at that site was set to zero [16]. Our study simulated the forces acting on the hip during the stance phase of walking [17].…”
Section: Methodsmentioning
confidence: 99%
“…The boundary condition was set as a fixation at the distal end of the femur, and the displacement along the x -, y - and z -axes at that site was set to zero [16]. Our study simulated the forces acting on the hip during the stance phase of walking [17].…”
Section: Methodsmentioning
confidence: 99%
“…Reports involving radiographic surveys have found that the cut-out rate of lag screws is higher in the superior region than in other regions 2) . Some reports have suggested that the central-inferior region is the ideal position for the lag screw 9 10 11 12) . One explanation for this difference is that when the screw is placed in the inferior region, it does not damage the area where the bone is the strongest.…”
Section: Discussionmentioning
confidence: 99%
“…According to the most widely used guidelines at present, some studies report that TAD less than 25 mm is recommended 6 7 8) . The results of many retrospective studies have not been in uniform agreement on the optimal position of screws, and there is no persuasive basis to explain the correlation between these specific screw positions and a good prognosis 9 10 11 12) . In addition, some studies have reported a positive correlation between bone microarchitecture around screws and the pullout resistance of screws 13) .…”
Section: Introductionmentioning
confidence: 99%
“…The individual differences revealed that the FE model was satisfactorily validated. The boundary condition was set by xing the distal end of the femur, and the displacement along the x-, y-, and z-axes at that site was set to zero [7]. This study simulated the forces acting on the hip during the stance phase of walking [8].…”
Section: Boundary and Loading Conditionsmentioning
confidence: 99%